Autonomous mobile robot navigation in cluttered environment using hybrid Takagi-Sugeno fuzzy model and simulated annealing algorithm controller. (3rd October 2016) - Pandey, Anish; Parhi, Dayal R.
Abstract : Purpose: This paper aims to design a Takagi–Sugeno fuzzy model with a simulated annealing hybrid algorithm (fuzzy-SAA) that was implemented for mobile robot navigation and obstacle avoidance in a cluttered environment. Design/methodology/approach: The SAA is used to optimize the output parameters of the fuzzy controller. The ultrasonic range finder sensor and sharp infrared range sensor are used for calculating the different obstacle distances, such as front, right and left obstacle distance, for selecting the suitable steering angle control command in the environment. Findings: The simulation and experimental results show the proposed method is feasible and valid for a wheeled mobile robot moving in a cluttered environment. Originality/value: The developed fuzzy-SAA hybrid algorithm provides better results (in terms of navigation path length and time) as compared to previous works, which verifies the effectiveness and efficiency of the developed hybrid algorithm.